Civic Returns to Education: Voter Turnout in Ireland - Ma, Yuanyuan (The Economic and Social Review, 2017)
Education is one of the most often cited explanations for voter turnout. However, the international evidence that estimates the causal effect of education on voter turnout is mixed. There is no evidence for such a causal effect in Ireland. Using data from the Irish Longitudinal Study on Ageing (TILDA), and employing the instrumental variable (IV) probit model, we investigate whether education has a causal effect on individuals’ political participation in their later lives. We find that individuals with more education are more likely to vote in the general election. The effects are larger for individuals whose parents have only primary education or below, and for individuals growing up in a poor family. The findings provide motivations for increasing targeted public supports in education for students coming from a disadvantaged family.